Ethanolic extract of Annona muricata leaf and its effect on the liver - Nweke, Elizabeth O; Ndukwe, Godwin U; Opara, Julia K (Journal of Drug Delivery and Therapeutics, 2019)
The effect of ethanolic extract of Annona muricata leaf on the liver of albino rats were investigated in this study. Twenty (20) male albino rats weighing between 180-200 g were used in this study. The animals were divided into groups A, B, C and D. Group A was treated with 2 ml/kg body weight of distilled water, Group B was treated with 100 mg/kg body weight of the extract, Group C was treated with 200 mg/kg body weight of the extract and Group D was treated with 300 mg/kg body weight of the extract. The treatments were given orally and lasted for a period of 30 days. After the last day of treatment, the animals were sacrificed and the liver harvested, weighed and fixed in 10% formal saline for histological studies. Blood samples were collected through cardiac puncture for biochemical analysis. Data were analysed using one-way ANOVA and SPSS version 2.0. Results showed a significant (P<0.05) increase in liver weight when compared to control and a significant (P<0.05) increase in serum levels of ALP, ALT and AST at highest dose. Histopathological findings showed distortions of the liver cytoarchitecture with the highest dose having a more significant effect. Consumption of ethanolic extract of A. muricata leaf at higher doses has the potential of causing liver damage. Thus, its consumption should be regulated or better still taken at lower doses. Keywords: Annona muricata; Liver; Liver enzymes; Albino rats